Follow-up after post-partum psychiatric emergency department visits: an equity-focused population-based study in Canada. (May 2022) - Barker, Lucy C; Brown, Hilary K; Bronskill, Susan E; Kurdyak, Paul; Austin, Peter C; Hussain-Shamsy, Neesha; Fung, Kinwah; Vigod, Simone N
Summary: Background: Emergency department visits for a psychiatric reason in the post-partum period represent an acute need for mental health care at a crucial time, but little is known about the extent of timely outpatient follow-up after these visits or how individual and intersecting social determinants of health influence this outcome. This study aimed to examine outpatient mental health care follow-up by a physician in the 30 days after an individual attended the emergency department for a psychiatric reason in the post-partum period and understand how social determinants of health affect who receives follow-up care. Methods: In this population-based cohort study, routinely collected health data from Ontario, Canada were accessed through ICES to identify all post-partum individuals whose sex was listed as female on their health card and who had attended an emergency department in Ontario before the COVID-19 pandemic for a psychiatric reason. Individuals admitted to hospital at the time of the emergency department visit, who died during the visit, or who left without being seen were excluded from the study. Ethnicity data for individuals were not collected. The primary outcome was the proportion of individuals with any outpatient physician (psychiatrist or family physician) visit for a mental health reason within 30 days of the index emergency department visit. Family physician mental health visits were identified using a validated algorithm for Ontario Health Insurance Plan-billed visits and mental health diagnostic codes for community health centre visits. We examined the associations between social determinants of health (age, neighbourhood income, community size, immigration, neighbourhood ethnic diversity) and who received an outpatient mental health visit. We used modified Poisson regression adjusting for the other social determinants of health, clinical, and health services characteristics to examine independent associations with follow-up, and conditional inference trees to explore how social determinants of health intersect with each other and with clinical and health services characteristics in relation to follow-up. Findings: We analysed data collected between April 1, 2008, and March 10, 2020, after exclusions we identified 12 158 people who had attended the emergency department for a psychiatric reason in the post-partum period (mean age 26·9 years [SD 6·2]; range 13–47); 9848 individuals lived in an urban area, among these 1518 (15·5%) were immigrants and 2587 (26·3%) lived in areas with high ethnic diversity. 5442 (44·8%) of 12 158 individuals received 30-day follow-up. In modified Poisson regression models, younger age, lower neighbourhood income, smaller community size, and being an immigrant were associated with a lower likelihood of follow-up. In the CTREE, similar variables were important, with several intersections between social determinants of health and between social determinants of health and other variables. Interpretation: Fewer than half of emergency department visits for a psychiatric reason in the post-partum period were followed by timely outpatient care, with social-determinants-of-health-based disparities in access to care. Improvements in equitable access to post-emergency department mental health care are urgently needed in this high-risk post-partum population. Funding: Department of Psychiatry, University of Toronto; Canadian Institutes of Health Research.